The antimalarial activity of the extract of the neem leaves (Azadirachta indica, A. Juss) on Plasmodium falciparum in vitro - Hanifah Yusuf; . Suryawati; . Maryatun (Syiah Kuala University, 2011)
. Malaria is a life-threatening disease due to the development of resistance by the most lethal causative parasitic species mainly Plasmodium falciparum. One of a great challenges in malaria controlling program is P.falciparum that has been resistant to the most commonly available antimalarials. New drugs with specific structures and mode of actions are urgently required to treat sensitive and drug-resistant strains of malaria parasites. This study was designed to know the antimalarial activity of the extract of the neem leaves (Azadirachta indica A.Juss) on the growth stages of P. falciparumFCR-3. The experimental laboratoric study used “post-test only with control design”. RPMI 1640 used as culture medium for cultivation of P. falciparum. Treated drug was the extract of neem leaves dissolved in dimethylsulfooxide and prepared into 7 levels concentration (3,125; 6,25; 12,5; 25; 50; 100 and 200 ug/mL). Negative control was culture medium with the malarial parasites. After cultured, synchronized, micromalarialculture were divided into control and treated groups then incubated in CO2 Candle Jar at 370 C for 72 hour. Each 8 hour the percentage of parasitemia were measured for observing the activity of the extract on the growth stages of P. falciparum. After incubation, supernatant fluid was removed without disturbing the erythrocyte layer. Parasitemia was calculated by made the thin blood smear from the erythrocyte layer and stained with 10% Giemsa for 30 minutes. The antimalarial activity of the extract was calculated by counted the fifty percent of growth inhibition 50 (IC50) using probit analysis. The result showed that the neem leaves extract can inhibit the growth of P. falciparum FCR-3 on mature schizont stage and the fifty percent inhibitory concentration (IC50) of the extract was 3,86 µg/ml after 32 hour incubating. The result indicated that the extract has an antimalarial activity on P. falciparumFCR-3 in vitro